Technological and commercial maturity of aviation biofuels: Emerging options to produce jet from lignocellulosic biomass - Mawhood,RK; Gazis,E; Hoefnagels,R; De,Jong S; Slade,R (2015)
The aviation sector is responsible for an increasing share of anthropogenic CO2 emissions. Wider adoption of aviation biofuels (biojet) is imperative for the reduction of greenhouse-gas emissions, however it represents a radical departure from the existing technological regime of petroleum-based fuels. Further market deployment will require significant techno-economic breakthroughs, as well as adaptation of the existing supply chains and infrastructure.Although a large number of technologies which have the capability to produce such fuels are being developed, many of these are unlikely to be suitable for EU-based production in the short-term. Biojet production pathways vary considerably in terms of their techno-economic features, with the most highly developed being in the very early stages of commercialisation.In this article, the authors map current development and manufacturing efforts within five emerging biojet technological pathways. The research draws upon a comprehensive review of the international academic and grey literature in order to characterise the pathways according to their technological and commercial maturity, as well as progress towards international certification.By implementing the Fuel Readiness Level (FRL) methodology, the authors provide insights regarding not only the current status of the biojet sector, but also potential opportunities for the short-term development of supply chains in the EU.